A NEW GENUS AND A NEW SPECIES OF PTEROMALIDAE (HYMENOPTERA) ASSOCIATED WITH SERICULTURE IN ASSAM (INDIA) - NARENDRAN, T. C.; SAHU, MAMANI; DAS, PROBODH KUMAR (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2002)
A new genus viz. Neotoxeumorpha Narendran gen. nov. and new species Neotoxeumorpha exoristae Narendran sp. nov. are described and affinities discussed. The new genus comes very close to the genus Toyeumorpha Girault in the structure of the gastral petiole but differs from it in having pronotum with dorsal carina, forewing without basal line of setae; first gastral tergite produced posteriorly reducing the median length of second gastral tergite and funicular segments distinctly transverse. N exorisiae parasitise Exorista sorbillans (Wied.) attacking Muga silk worm in Assam.